Design and development of a solar energy system for use in home - Ooi, Ching Hui (2019)
With the lack of natural resources available in Singapore and the increasing need to find alternative renewable energy sources. Solar energy is the most practical choice of renewable source for Singapore with its geographical location that provides an average annual solar irradiance of 1,589kWh/m2/year. Despite the limited land constraints in Singapore, the SolarNova programme was launched to promote the increase the installations of solar panels onto roofs of public housing managed by the Housing and Development Board (HDB) and government sites. Water surfaces have also been tapped on with pilot projects of the creating a floating solar-cell test bed, 1.5 times the size of a football field which also happens to be the world’s largest floating test bed for solar-cells. This project is hence based on the idea of creating a solar energy system that will be able to power loads used at home. The project will be designed to be low-power and low-cost to be suitable for home use.